Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Efektivitas Pembelajaran di SMA Yayasan Perguruan Istiqomah - Sari, Devi Permata; Setiawan, Hasrian Rudi (EL-EMIR Institute, 2025)
This study is intended to examine the approaches applied by Islamic Religious Education (PAI) teachers in improving the quality of learning in schools with a full day school system. The background of this research stems from the central role of PAI in shaping students’ personality, noble character, and religious values, as well as practical challenges in the field such as limited strategies, media constraints, and intensive school activities. This research employed a qualitative descriptive approach through observation, interviews, and documentation at SMA Yayasan Perguruan Istiqomah Islamic Full Day School. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while validity was ensured through triangulation and member checks. The findings indicate that PAI teachers applied diverse methods, integrated Islamic values into the curriculum, utilized simple digital media, implemented religious habituation, and provided role modeling. Supporting factors include school commitment, parental involvement, and student motivation, while the main obstacles are tight schedules, student fatigue, and limited technological facilities. This study emphasizes the importance of varied, interactive, contextual, and digitally adaptive PAI learning strategies to strengthen the internalization of Islamic values and foster increased student learning motivation.